2005
DOI: 10.1111/j.1348-0421.2005.tb03745.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Genotypes and the p53 Codon 72 Polymorphism in Cervical Cancer of Northeastern Thailand

Abstract: Cervical cancer is the most common female cancer in Northeastern Thailand (2) and is still the highest cause of mortality in females of this region (23). Our previous study has indicated that sexual behavior and smoking were risk factors for this cancer (19). In addition, we must pay attention to human papillomavirus (HPV) infection that is the most critical risk for cervical cancer (9, 18).HPV comprises so many strains; they are classified into a low-risk group (such as ) and a high-risk group (such as . Cerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
(25 reference statements)
2
18
1
1
Order By: Relevance
“…As for the prevalence of the various types of HPV, the general experience is the high prevalence of HPV-16 followed by HPV-18 (Chichareon et al, 1998;Settheetham-Ishida et al, 2005;Suthipintawong et al, 2011); however, our results indicated a rather high prevalence of HPV-58 (17.8%) in SCCA. HPV-58 is not rare in Asian women with normal cervical cytology; its prevalence being <1% in Thailand, Vietnam, Japan and Korea (Domingo et al, 2008;Konno et al, 2008) and 1~2% in Taiwan and China (Shi et al, 2008;Tay et al, 2008).…”
Section: Discussioncontrasting
confidence: 55%
“…As for the prevalence of the various types of HPV, the general experience is the high prevalence of HPV-16 followed by HPV-18 (Chichareon et al, 1998;Settheetham-Ishida et al, 2005;Suthipintawong et al, 2011); however, our results indicated a rather high prevalence of HPV-58 (17.8%) in SCCA. HPV-58 is not rare in Asian women with normal cervical cytology; its prevalence being <1% in Thailand, Vietnam, Japan and Korea (Domingo et al, 2008;Konno et al, 2008) and 1~2% in Taiwan and China (Shi et al, 2008;Tay et al, 2008).…”
Section: Discussioncontrasting
confidence: 55%
“…Among healthy women, an HPV infection was able to clear within 1-2 years (Klug et al, 2009;Schiffman et al, 2007) and <1% of HPV-positive women would go on to develop cervical cancer (Josefsson et al, 2000;Nagpal et al, 2002). The current report indicates that the involvement of other factors such as sexual behavior, personal and partner smoking habits and genetic backgrounds are likely co-factors with HPV for an increased risk of developing cervical cancer (Settheetham-Ishida et al, 2004;Settheetham-Ishida et al, 2005;Au et al, 2007;Almonte et al, 2008).…”
Section: Discussionmentioning
confidence: 62%
“…The prevalence of HPV infection among patients (85.9%) and controls (14.1%) seems higher compared to the previous study reporting the positivity rate 12% and 78% for the patients and controls, respectively. This may be attributable to the detection of only high risk HPV infections in the latter study (Settheetham-Ishida et al, 2005), a further HPV-typing will clear the gap of the prevalence. HPV infection was also detected in the controls indicated that not all of the HPV-infected women developed cervical cancer.…”
Section: Discussionmentioning
confidence: 82%
“…The following materials are necessary to analyze the p53 mutation: laboratory coats, gloves, Pipetman (model numbers p2, p20, p200, and p1000), sterile and UV-irradiated pipette tips, sterile stings, thermocycler with accompanying PCR tubes, a gel electrophoresis power unit, polyacrylamide gel apparatus consisting of glass plates (20 cm 3 20 cm 3 0.5 mm), clamps, tape, and spacers, Whatman FTA cards, Taq polymerase (Applied Biosystems, USA), dNTPs (Invitrogen, USA), primers: (20 lM oligo p53 5 0 CCCGGACGATATTGAACA 3 0 forward; 5 0 AGAAGCCCAGACGGAAAC 3 0 reverse [13], 25 mM MgCl 2 (Sigma), acrylamide, and bisacrylamide (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…The primers used were as follows: 5 0 CCCGGACGATATTG AACA3 0 forward; 5 0 AGAAGCCCAGACGGAAAC 3 0 reverse [13].…”
Section: Pcrmentioning
confidence: 99%